PENGARUH METODE PEMBELAJARAN AKTIF TERHADAP MENINGKATKAN MAHARAH AL-KALAM SISWA SMP IT WAHDAH ISLAMIYAH MAKASSAR - Azizah Nurul Izzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: (1) describe the implementation of active learning methods at SMP IT WahdahIslamiyah Makassar, (2) describe the Maharah Al Kalam (speaking skills) of students at the school, and(3) determine whether active learning methods significantly influence the improvement of Maharah AlKalam among eighth-grade students at SMP IT Wahdah Islamiyah Makassar. This research uses aquantitative approach with simple linear regression analysis. The sampling technique used is saturatedsampling with a total of 60 student participants. Data were collected through observation sheets,questionnaires, direct tests, interviews, and documentation.The results of the study indicate that theimplementation of the active learning method at the school falls into the moderate category. Although thismethod has been applied, student participation in activities such as discussions, presentations, andquestion-and-answer sessions remains uneven, thus the effectiveness of the method has not yet reachedan optimal level. Meanwhile, the students’ Maharah Al-Kalam (speaking skills) also fall into the moderatecategory, with an average score of 80.67. Students have demonstrated the ability to speak in Arabicusing grammatically correct sentence structures; however, they still encounter challenges related tofluency, clarity of articulation (makhraj al-huruf), and intonation. Regression analysis shows that the activelearning method has a positive and significant influence on students’ Maharah Al-Kalam, with acontribution rate of 35.5%, while the remaining 66.5% is influenced by other factors such as psychologicalconditions and the learning environment. These findings emphasize the importance of developing activelearning strategies and fostering intensive involvement of both teachers and students in the learningprocess to enhance students speaking abilities optimally.